1988
DOI: 10.1128/jvi.62.2.496-500.1988
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus preterminal protein synthesized in COS cells from cloned DNA is active in DNA replication in vitro

Abstract: Replication of the DNA genome of human adenovirus serotype 2 requires three virus-encoded proteins. Two of these proteins, the preterminal protein (pTP) and the adenovirus DNA polymerase, are transcribed from a single promoter at early times after virus infection. The mRNAs for these proteins share several exons, including one encoded near adenovirus genome coordinate 39. By using plasmids containing DNA fragments postulated to encode the various exons of pTP mRNA, the contributions of each exon to the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
1995
1995

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…The N-terminal region is supposed to be involved in this specific Ad DNA-nuclear matrix interaction that is probably important for virus multiplication. An essential function for the pTP N terminus is in agreement with earlier reports that mutations in this region affect pTP functioning in vivo (17,41) and in vitro (35,36). Interestingly, the sequence motif YSRLRYT (codons 104 through 110), which was recently reported to be conserved among all DNA-terminal proteins studied so far (21), is also located in this region.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The N-terminal region is supposed to be involved in this specific Ad DNA-nuclear matrix interaction that is probably important for virus multiplication. An essential function for the pTP N terminus is in agreement with earlier reports that mutations in this region affect pTP functioning in vivo (17,41) and in vitro (35,36). Interestingly, the sequence motif YSRLRYT (codons 104 through 110), which was recently reported to be conserved among all DNA-terminal proteins studied so far (21), is also located in this region.…”
Section: Discussionsupporting
confidence: 90%
“…was demonstrated to encode three amino acids (Met-Ala-Leu) that constitute a common N terminus for pTP and Ad pol (46). This leader appeared to be essential for production of functional pTP and Ad pol in COS cells (35,45). Transient expression systems have also been used to identify the nuclear localization signals of pTP and Ad pol (58,59) and to map regions in both proteins that are essential for Ad DNA replication (9,16).…”
mentioning
confidence: 99%
“…Initiation was measured by formation of 32P-labeled pTP-dCMP complexes after incubation with [_-32P]dCTP (15 ,Ci,400 Ci/mmol). Labeled initiation complexes were immunoprecipitated and analyzed by sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) (21). Quantitative densitometric analysis was performed on an Ultroscan XL laser densitometer (LKB Instruments, Inc., Rockville, Md.).…”
Section: Methodsmentioning
confidence: 99%
“…Calculated relative activities of various pTP mutants. The activities were compared with that of the wild type (J-pTP) by the densitometric tracings of autoradiographs of initiation and elongation assays.b This mutant was previously described by Pettit et al(21). Data shown are derived at a nonpermissive temperature of 38°C.…”
mentioning
confidence: 99%
“…The other primary transcription unit (E2B), encoding an mRNA of some 22 kb, allows the expression of both the pTP and pol proteins following a complex splicing mechanism. Recent investigations have suggested that functional pol and pTP require sequences at map position 39 (in a minor exon) as well as those in the main body of the transcripts (Shu et al, 1987;Pettit et al, 1988;Stunnenberg et al, 1988). Indeed, earlier attempts to express functional pol appeared to have been unsuccessful because constructs were used with an ATG codon at base 8367 rather than an ATG at base 14114.…”
Section: Protein Factors Required For Adenovirus Dna Replicationmentioning
confidence: 99%